Preparation method of rare earth alloying modified 6061 aluminum alloy semi-solid casting material

Through the preparation method of rare earth alloy modified 6061 aluminum alloy, combined with rare earth composite particles and specific process treatment, the problems of coarse grains, uneven structure and many defects in semi-solid casting are solved, and high-strength and high-performance casting materials are achieved.

CN119592836APending Publication Date: 2025-03-11NINGXIA UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411775662.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing 6061 aluminum alloy has problems such as coarse grains, uneven structure, insufficient mechanical properties and many internal defects in the semi-solid casting process, making it difficult to meet the needs of high-performance manufacturing.

Method used

Through the preparation method of rare earth alloy modified 6061 aluminum alloy, a specific proportion of rare earth composite particles are added, and a biaxial mechanical stirring and partition cooling system is used to control the temperature and grain distribution of the liquid-solid phase zones, and solid solution and aging are carried out.

Benefits of technology

It significantly improves the tensile strength and hardness of aluminum alloys, optimizes grain refinement and tissue uniformity, reduces internal defects, and meets the needs of high-strength and high-performance castings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592836A_ABST
    Figure CN119592836A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of metal materials, and discloses a preparation method of a rare earth alloying modified 6061 aluminum alloy semi-solid casting material which comprises the following components in percentage by weight: 0.8-1.2% of zinc; 0.5%-0.7% of magnesium; 0.4% to 0.6% of silicon; 0.05% to 0.1% of cobalt; 0.3%-0.5% of lithium; 0.3%-0.5% of copper; 0.1%-0.3% of yttrium; 0.05% to 0.1% of molybdenum; 0.02% to 0.08% of titanium; 93%-95% of aluminum; comprising the following steps that S1, rare earth elements yttrium, molybdenum and lanthanum are mixed according to the proportion of 1: 1: (0.5-1), and rare earth composite particles with the particle size ranging from 0.01 mm to 0.03 mm are prepared through ball milling, high-temperature sintering and airflow atomization technologies; the structure uniformity and grain refinement effect of a semi-solid liquid-solid two-phase region are optimized by controlling the accurate proportion of strengthening elements and combining with the addition of rare earth composite particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal materials, in particular to a method for preparing a rare earth alloyed modified 6061 aluminum alloy semi-solid casting material. Background Art

[0002] As a typical heat-treatable and strengthened aluminum alloy, 6061 aluminum alloy is widely used in aerospace, automobile manufacturing, mold industry and other fields due to its excellent mechanical properties, high corrosion resistance and low density.

[0003] However, the existing 6061 aluminum alloy still has multiple technical bottlenecks in the semi-solid casting process, which limits its further promotion in the field of high-performance manufacturing.

[0004] First, the grains of traditional 6061 aluminum alloy are relatively coarse, especially in the semi-solid liquid-solid coexistence zone. Since the solid phase particles are prone to agglomeration and growth, the grain structure of the casting is uneven, which significantly reduces the mechanical properties of the material (such as tensile strength, hardness and elongation). Although the existing technology attempts to add refiners or control the grains through mechanical stirring processes, the effect is limited and it is difficult to meet the application requirements of complex high-strength components.

[0005] Secondly, the internal defect problem of 6061 aluminum alloy is more prominent. In semi-solid casting, due to uneven cooling control or unstable distribution of solid phase particles, defects such as pores, shrinkage and inclusions are easily generated in the casting, which seriously weaken the internal quality and fatigue performance of the casting. Uniform cooling or mold improvement is often used in the prior art to optimize the internal structure, but the control accuracy of these methods is insufficient, resulting in large fluctuations in casting quality. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a method for preparing a rare earth alloyed modified 6061 aluminum alloy semi-solid casting material, which solves the problems of the prior art in terms of coarse grains, uneven structure, insufficient mechanical properties and many internal defects.

[0007] To achieve the above objectives, the present invention is implemented through the following technical scheme: rare earth alloying modified 6061 aluminum alloy semi-solid casting material, including by weight percentage: zinc 0.8%-1.2%; magnesium 0.5%-0.7%; silicon 0.4%-0.6%; cobalt: 0.05%-0.1%; lithium 0.3%-0.5%; copper 0.3%-0.5%; yttrium 0.1%-0.3%; molybdenum 0.05%-0.1%; titanium 0.02%-0.08%; aluminum 93%-95%.

[0008] A method for preparing a rare earth alloy modified 6061 aluminum alloy semi-solid casting material comprises the following steps:

[0009] S1, rare earth elements yttrium, molybdenum and lanthanum are mixed in a ratio of 1:1:0.5-1, and rare earth composite particles with a particle size of 0.01 mm-0.03 mm are prepared by ball milling, high temperature sintering and air flow atomization process;

[0010] S2. After the high-purity aluminum ingot is completely melted in an induction melting furnace at 700℃-750℃, strengthening elements are added in the following order:

[0011] a. When the melt temperature is maintained at 710℃-730℃, magnesium, silicon and zinc are added in sequence;

[0012] b. Then add copper and manganese;

[0013] c. Finally, add rare earth composite particles;

[0014] S3, cooling the melt to a liquid-solid two-phase region of 600°C-630°C, and stirring with a biaxial mechanical stirring device to make the solid phase particles evenly distributed;

[0015] S4, injecting the treated melt into a metal mold preheated to 380°C-420°C, and using a zone cooling system to control the temperature gradient to 10°C / mm-20°C / mm, so that the casting completes directional solidification;

[0016] S5. Perform heat treatment on the casting, including solution treatment and aging treatment.

[0017] Specifically, S1: Preparation of rare earth composite particles: rare earth elements yttrium (Y), molybdenum (Mo) and lanthanum (La) are mixed in a ratio of 1:1:0.5-1. This ratio ensures the synergistic effect between the rare earth elements. Yttrium mainly plays a role in grain refinement, molybdenum provides thermal stability, and lanthanum can promote the homogenization of the matrix structure.

[0018] The mixed rare earth is mechanically ball-milled at a speed of 400 rpm through a ball mill to uniformly disperse the rare earth particles and improve the reaction activity of the particles.

[0019] The ball-milled mixed powder is sintered in a high-temperature sintering furnace at a temperature of 450°C-500°C for 2-4 hours. This process can further enhance the internal structural stability of the rare earth composite particles.

[0020] The sintered rare earth blocks are atomized into tiny particles with a particle size of 0.01mm-0.03mm using an air flow atomization process at a high temperature of 700℃-720℃ and a high-speed air flow (air pressure 0.3MPa-0.5MPa).

[0021] S2: Step-by-step addition of strengthening elements:

[0022] A high-purity aluminum ingot (purity ≥ 99.9%) is placed in an induction melting furnace and heated to 700°C-750°C to ensure that the aluminum ingot is completely melted and forms a pure aluminum matrix melt.

[0023] Step a: When the melt temperature is stabilized at 710° C.-730° C., magnesium (0.5%-0.7%), silicon (0.4%-0.6%) and zinc (0.8%-1.2%) are added in sequence. These elements dissolve rapidly and form an initial strengthening phase with the aluminum matrix.

[0024] Step b: Adding copper (0.3%-0.5%) and manganese (0.05%-0.1%), these elements enhance the heat treatment responsiveness and fatigue resistance of the alloy.

[0025] Step c: Finally, add the prepared rare earth composite particles and stir at a speed of 400 rpm-600 rpm using a high shear mechanical stirrer to ensure that the rare earth particles are evenly dispersed.

[0026] S3: Liquid-solid two-phase region treatment and stirring: The melt is gradually cooled to 600°C-630°C. This temperature range is in the liquid-solid two-phase region of the aluminum alloy, ensuring the coexistence of the liquid phase and the solid phase. The content of the solid phase particles is about 30%-50%.

[0027] A biaxial mechanical stirring device was used for stirring, the stirring speed was controlled at 300 rpm-400 rpm, and the stirring direction was switched every 5 minutes to enhance the uniform distribution of the solid phase particles.

[0028] The stirring time is 12-15 minutes. During the stirring process, the melt surface is protected by injecting a mixed gas of argon and sulfur hexafluoride (3:1) to prevent oxidation.

[0029] S4: Mold pouring and directional solidification: The treated melt is injected into a metal mold preheated to 380℃-420℃, and the mold surface is coated with a nano-ceramic-based thermal insulation coating to reduce the risk of thermal shock.

[0030] Cooling water is introduced into the bottom of the mold partition cooling system, and the flow rate is controlled at 2L / min-5L / min; cooling gas (argon or air) is introduced into the top, and the flow rate is 1.0m 3 / h-2.0m 3 / h, and the cooling gradient is controlled at 10℃ / mm-20℃ / mm.

[0031] Directional solidification is achieved by using zone cooling, and the casting gradually solidifies from the bottom to the top, reducing the formation of shrinkage and pores.

[0032] S5: Heat treatment of castings:

[0033] Solution treatment: slowly heat the casting to 500℃-520℃, keep it warm for 1 hour, then heat it to 540℃-560℃, and keep it warm for 1.5-2 hours. The purpose is to make the strengthening elements fully dissolved in the aluminum matrix to form a uniform supersaturated solid solution.

[0034] Aging treatment: In the first stage, the temperature is kept at 160℃-170℃ for 4-6 hours, and in the second stage, the temperature is increased to 180℃-190℃ and kept for 2-3 hours to promote the formation of precipitation strengthening phase.

[0035] Preferably, in step S1, the temperature of high-temperature sintering in a fluidized bed is 400°C-500°C, the sintering time is 2-4 hours, and the temperature of air flow atomization is 680°C-720°C.

[0036] Preferably, the proportions of strengthening elements added in step S2 are: 0.5%-0.8%, 0.4%-0.7% and 0.8%-1.5% for magnesium, 0.4%-0.7% and 0.8%-1.5% for silicon and zinc, and 0.2%-0.5% and 0.05%-0.12% and 0.05%-0.12% and 0.2%-0.5% and 0.05%-0.12% respectively for copper and manganese.

[0037] Preferably, the rare earth composite particles in step c of S2 are added in an amount of 0.3%-0.6% of the total weight of the aluminum alloy. When stirred by a high shear mechanical stirrer, the speed of the stirrer is controlled at 400rpm-600rpm, and the stirring time is 8-12min.

[0038] Preferably, in step S3, the stirring speed is 250 rpm-400 rpm, the stirring time is 12-15 min, and the time interval for switching the rotation direction during the stirring process is 3-5 min.

[0039] Preferably, the surface protection of the melt during the cooling process of the liquid-solid two-phase region in step S3 is carried out by using a mixed gas of argon and sulfur hexafluoride, the mixing ratio of which is 3:1-5:1, and the injection gas flow rate is 0.3m 3 / h-0.7m 3 / h.

[0040] Preferably, the cooling method of the zoned cooling system in step S4 includes cooling the bottom by cooling water flow and cooling the top by cooling gas.

[0041] Preferably, the cooling water flow rate is controlled to be 2L / min-5L / min, and the cooling gas flow rate is controlled to be 1.0m 3 / h-2.0m 3 / h.

[0042] Preferably, the heating rate of the solution treatment in step S5 is 5°C / min-15°C / min, the holding time of the first stage of aging treatment at 160°C-170°C is 4-6 hours, and the holding time of the second stage after heating to 180°C-190°C is 2-3 hours.

[0043] The invention provides a method for preparing a rare earth alloyed modified 6061 aluminum alloy semi-solid casting material.

[0044] It has the following beneficial effects:

[0045] 1. The present invention significantly improves the tensile strength and hardness of the aluminum alloy by precisely controlling the proportion of strengthening elements and combining the addition of rare earth composite particles, optimizes the organizational uniformity and grain refinement effect of the semi-solid liquid-solid two-phase region, wherein the tensile strength reaches 340MPa and the hardness is increased to 115HV, meeting the use requirements of high-strength and high-performance castings, while enhancing the stability of the material in the semi-solid casting process.

[0046] 2. The present invention achieves significant grain refinement of aluminum alloy by optimizing the particle size of rare earth particles and controlling the cooling gradient, and refines the grain size from 14 μm in conventional processes to 9 μm, thereby significantly improving the mechanical properties and organizational uniformity of the material.

[0047] 3. The present invention adopts optimized liquid-solid two-phase zone treatment and zone cooling process, and the cooling gradient reaches 20℃ / mm, which greatly reduces the number of internal defects of castings from 15 / 100cm in ordinary process. 2 Reduced to 5 / 100cm 2 , significantly improving the internal quality and reliability of castings. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 It is a schematic diagram of the preparation method steps of the present invention. DETAILED DESCRIPTION

[0049] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] Please refer to the attached Figure 1 , Example 1: Optimization of rare earth composite particle size

[0051] Process details:

[0052] Preparation of rare earth composite particles: Yttrium (Y), molybdenum (Mo), and lanthanum (La) were mixed in a ratio of 1:1:0.8 and stirred at 400 rpm for 6 hours using a high-energy ball mill. The sintering temperature was 450°C for 3 hours; the atomization temperature was 700°C, and the particle size was controlled to be 0.01-0.02 mm.

[0053] Strengthening elements added: magnesium, silicon, zinc in proportions of 0.6%, 0.5%, 1.2% respectively, copper and manganese in proportions of 0.3%, 0.1% respectively.

[0054] Liquid-solid two-phase treatment: the temperature was controlled at 615°C, the stirring speed was 300 rpm, and the stirring time was 12 minutes.

[0055] Cooling system: mold preheating temperature 400℃, cooling water flow rate 3.0L / min, cooling gas flow rate 1.8m 3 / h.

[0056] Test results:

[0057] Tensile strength: 328MPa;

[0058] Elongation: 9.8%;

[0059] Hardness: 107HV;

[0060] Grain size: 12μm;

[0061] Internal defects: 6 / 100cm 2 .

[0062] Summary: Rare earth particles with smaller particle size significantly improve the grain refinement effect and significantly improve the mechanical properties; the tensile strength and hardness are excellent, but the elongation is slightly reduced.

[0063] Example 2: Adjustment of the ratio of rare earth composite particles

[0064] Process details:

[0065] Preparation of rare earth composite particles: Yttrium, molybdenum and lanthanum are mixed in a ratio of 1:1:0.5, and the particles with a particle size of 0.02-0.03 mm are obtained by air flow atomization. The sintering temperature is 480°C for 4 hours; the atomization temperature is 720°C.

[0066] Strengthening elements added: magnesium, silicon, zinc in proportions of 0.7%, 0.6%, 1.5% respectively, copper and manganese in proportions of 0.4%, 0.05% respectively.

[0067] Liquid-solid two-phase treatment: temperature is 620°C, stirring speed is 350 rpm, and stirring time is 15 minutes.

[0068] Cooling system: mold preheating temperature 420℃, cooling gradient 15℃ / mm.

[0069] Test results:

[0070] Tensile strength: 320MPa;

[0071] Elongation: 10.5%;

[0072] Hardness: 102HV;

[0073] Grain size: 14μm;

[0074] Internal defects: 10 / 100cm 2 .

[0075] Summary: Adjusting the rare earth ratio increases the elongation, which is suitable for situations with high plasticity requirements; the tensile strength is slightly reduced, and the grain refinement effect is slightly inferior.

[0076] Example 3: Optimization of strengthening element ratio

[0077] Process details:

[0078] Strengthening elements added: magnesium, silicon, zinc in proportions of 0.5%, 0.4%, 1.0% respectively, copper and manganese in proportions of 0.3%, 0.08% respectively.

[0079] Preparation of rare earth composite particles: yttrium, molybdenum, and lanthanum in a ratio of 1:1:1, atomization temperature of 700°C, and particle size of 0.02 mm.

[0080] Liquid-solid two-phase treatment: temperature controlled at 600°C, stirring speed 400 rpm, stirring time 15 minutes.

[0081] Cooling system: mold cooling gradient 20℃ / mm.

[0082] Test results:

[0083] Tensile strength: 335MPa;

[0084] Elongation: 9.2%;

[0085] Hardness: 112HV;

[0086] Grain size: 10μm;

[0087] Internal defects: 5 / 100cm 2 .

[0088] Summary: After the proportion of strengthening elements is adjusted, the tensile strength and hardness reach the peak value; the grain refinement effect is the best, but the elongation is slightly reduced.

[0089] Example 4: Optimization of stirring parameters

[0090] Process details:

[0091] Liquid-solid two-phase treatment: stirring speed: 300 rpm; stirring direction switching interval 5 minutes; total stirring time 15 minutes.

[0092] Rare earth composite particles: yttrium, molybdenum, and lanthanum are prepared in a ratio of 1:1:0.8, and the particle size is 0.02 mm.

[0093] Cooling system: cooling gradient is 15℃ / mm, cooling water flow rate is 3.5L / min.

[0094] Test results:

[0095] Tensile strength: 330MPa;

[0096] Elongation: 9.7%;

[0097] Hardness: 109HV;

[0098] Grain size: 11μm;

[0099] Internal defects: 7 / 100cm 2 .

[0100] Summary: After optimizing the stirring parameters, the grain distribution is more uniform and the comprehensive mechanical properties are significantly improved; the defect distribution is slightly higher than that in Example 3.

[0101] Example 5: Cooling gradient optimization

[0102] Process details:

[0103] Cooling system: The cooling gradients were set to 10℃ / mm, 15℃ / mm, and 20℃ / mm to test the effects of different cooling conditions on material properties. Mold preheating temperature: 400℃.

[0104] Rare earth composite particles: yttrium, molybdenum and lanthanum are prepared in a ratio of 1:1:0.8, with a particle size of 0.02-0.03 mm.

[0105] Test results:

[0106] Cooling gradient 10℃ / mm:

[0107] Tensile strength: 318MPa; Elongation: 10.0%; Hardness: 106HV; Grain size: 14μm.

[0108] Cooling gradient 15℃ / mm:

[0109] Tensile strength: 322MPa; Elongation: 9.8%; Hardness: 108HV; Grain size: 12μm.

[0110] Cooling gradient 20℃ / mm:

[0111] Tensile strength: 328MPa; Elongation: 9.6%; Hardness: 110HV; Grain size: 10μm.

[0112] Summary: When the cooling gradient is 20℃ / mm, the grain refinement effect is the best, and the tensile strength and hardness are the highest; a lower cooling gradient is conducive to the improvement of elongation.

[0113] Comparative Experimental Design and Detailed Analysis

[0114] Experimental objective: To evaluate the combined effects of rare earth particle size, cooling gradient, and strengthening element ratio on alloy properties (tensile strength, elongation, hardness, grain size, and defect rate).

[0115] Explore the key influencing mechanisms of multi-parameter interactions on material properties.

[0116] Verify the performance superiority of rare earth alloyed modified 6061 aluminum alloy under specific process conditions.

[0117] Comparative experiment 1: Experimental variables

[0118] Rare earth particle size: 0.01mm, 0.02mm, 0.03mm;

[0119] Cooling gradient: 10℃ / mm, 15℃ / mm, 20℃ / mm.

[0120] The experimental design adjusted the rare earth particle size and cooling gradient under the same strengthening element ratio (0.6% magnesium, 0.5% silicon, 1.2% zinc) and process parameters.

[0121] Test tensile strength, elongation, hardness, grain size and defect rate.

[0122] Experimental data table

[0123]

[0124] Experimental analysis:

[0125] The smaller the particle size and the higher the cooling gradient, the higher the tensile strength and hardness, but the elongation decreases slightly. Under the conditions of particle size 0.01mm and cooling gradient 20℃ / mm, the comprehensive performance is the best: tensile strength 335MPa, hardness 115HV, grain size 9μm, and only 5 defects / 100cm 2 .

[0126] Comparative experiment 2:

[0127] Strengthening element ratio:

[0128] Magnesium: 0.5%, 0.6%, 0.7%;

[0129] Silicon: 0.4%, 0.5%, 0.6%;

[0130] Zinc: 1.0%, 1.2%, 1.5%;

[0131] Rare earth particle addition amount: 0.3%, 0.4%, 0.5%.

[0132] The experimental design adjusted the ratio of strengthening elements to rare earth particles and controlled the other parameters to be consistent (cooling gradient 20°C / mm, stirring speed 300rpm).

[0133] Test mechanical properties and microstructure.

[0134] Experimental data table

[0135]

[0136] Experimental analysis

[0137] With the increase of the proportion of strengthening elements (magnesium, silicon, zinc), the tensile strength and hardness are significantly improved, the grains are significantly refined, but the elongation is slightly reduced.

[0138] The performance is best when the rare earth particle ratio is 0.4%-0.5%, and the maximum tensile strength reaches 340MPa.

[0139] Comparative experiment 3:

[0140] Stirring speed: 250rpm, 300rpm, 400rpm;

[0141] Stirring time: 10 minutes, 12 minutes, 15 minutes;

[0142] Cooling gradient: 10℃ / mm, 15℃ / mm, 20℃ / mm.

[0143] Experimental design

[0144] The mechanical properties and internal defect distribution were tested by combining different stirring speeds, times and cooling gradients. The microstructure was observed using a scanning electron microscope.

[0145] Experimental data table

[0146]

[0147] Experimental analysis

[0148] Under the conditions of stirring speed of 300rpm and time of 15 minutes, the tensile strength and grain refinement effects are the best; the cooling gradient of 20℃ / mm further reduces the number of defects and makes the comprehensive performance reach the best state.

[0149] Overall experimental summary

[0150] The best combination parameters are: rare earth particle size: 0.01 mm; cooling gradient: 20°C / mm; strengthening element ratio: magnesium 0.7%, silicon 0.6%, zinc 1.5%, rare earth particles 0.5%; stirring speed: 300 rpm, stirring time: 15 minutes.

[0151] Comprehensive performance: tensile strength: 340MPa; elongation: 9.3%; hardness: 115HV; grain size: 9μm; internal defects: 5 / 100cm 2 .

[0152] Through multi-parameter optimization and in-depth comparative analysis, the preparation method of rare earth alloying modified 6061 aluminum alloy shows significant technical advantages in mechanical properties, grain refinement and defect control.

[0153] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. Rare earth alloying modified 6061 aluminum alloy semi-solid casting material, characterized in that: In terms of weight percentage, it includes: zinc 0.8%-1.2%; magnesium 0.5%-0.7%; silicon 0.4%-0.6%; cobalt: 0.05%-0.1%; lithium 0.3%-0.5%; copper 0.3%-0.5%; yttrium 0.1%-0.3%; molybdenum 0.05%-0.1%; titanium 0.02%-0.08%; aluminum 93%-95%.

2. A method for preparing a rare earth alloy modified 6061 aluminum alloy semi-solid casting material, according to the rare earth alloy modified 6061 aluminum alloy semi-solid casting material according to claim 1, characterized in that: The following steps are involved: S1, rare earth elements yttrium, molybdenum and lanthanum are mixed in a ratio of 1:1:0.5-1, and rare earth composite particles with a particle size of 0.01 mm-0.03 mm are prepared by ball milling, high temperature sintering and air flow atomization process; S2. After the high-purity aluminum ingot is completely melted in an induction melting furnace at 700℃-750℃, strengthening elements are added in the following order: a. When the melt temperature is maintained at 710℃-730℃, magnesium, silicon and zinc are added in sequence; b. Then add copper and manganese; c. Finally, add rare earth composite particles; S3, cooling the melt to a liquid-solid two-phase region of 600°C-630°C, and stirring with a biaxial mechanical stirring device to make the solid phase particles evenly distributed; S4, injecting the treated melt into a metal mold preheated to 380°C-420°C, and using a zone cooling system to control the temperature gradient to 10°C / mm-20°C / mm, so that the casting completes directional solidification; S5. Perform heat treatment on the casting, including solution treatment and aging treatment.

3. The method for preparing the rare earth alloyed modified 6061 aluminum alloy semi-solid casting material according to claim 2, characterized in that: In the step S1, the temperature of high-temperature sintering in the fluidized bed is 400°C-500°C, the sintering time is 2-4 hours, and the temperature of air flow atomization is 680°C-720°C.

4. The method for preparing the rare earth alloyed modified 6061 aluminum alloy semi-solid casting material according to claim 2, characterized in that: In the step S2, the proportions of strengthening elements added are: magnesium, silicon and zinc added in an amount of 0.5%-0.8%, 0.4%-0.7%, 0.8%-1.5%, and copper and manganese added in an amount of 0.2%-0.5% and 0.05%-0.12%, respectively.

5. The method for preparing the rare earth alloyed modified 6061 aluminum alloy semi-solid casting material according to claim 2, characterized in that: The rare earth composite particles added in step c of S2 are 0.3%-0.6% of the total weight of the aluminum alloy. When stirred by a high shear mechanical stirrer, the speed of the stirrer is controlled at 400rpm-600rpm, and the stirring time is 8-12min.

6. The method for preparing the rare earth alloyed modified 6061 aluminum alloy semi-solid casting material according to claim 2, characterized in that: In the step S3, the stirring speed is 250 rpm-400 rpm, the stirring time is 12-15 min, and the time interval for switching the rotation direction during the stirring process is 3-5 min.

7. The method for preparing the rare earth alloyed modified 6061 aluminum alloy semi-solid casting material according to claim 2, characterized in that: In the step S3, the surface protection of the melt during the cooling process of the liquid-solid two-phase region is carried out by using a mixed gas of argon and sulfur hexafluoride, the mixing ratio of which is 3:1-5:1, and the injection gas flow rate is 0.3m 3 / h-0.7m 3 / h.

8. The method for preparing the rare earth alloyed modified 6061 aluminum alloy semi-solid casting material according to claim 2, characterized in that: In the step S4, the cooling method of the zoned cooling system includes cooling the bottom by cooling water flow and cooling the top by cooling gas.

9. The method for preparing the rare earth alloyed modified 6061 aluminum alloy semi-solid casting material according to claim 8, characterized in that: The cooling water flow rate is controlled at 2L / min-5L / min, and the cooling gas flow rate is controlled at 1.0m 3 / h-2.0m 3 / h.

10. The method for preparing the rare earth alloyed modified 6061 aluminum alloy semi-solid casting material according to claim 2, characterized in that: The heating rate of the solution treatment in step S5 is 5°C / min-15°C / min, the first stage of the aging treatment is kept at 160°C-170°C for 4-6 hours, and the second stage is heated to 180°C-190°C and kept at 180°C-190°C for 2-3 hours.